2020
DOI: 10.21203/rs.2.15748/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Another piece of the Zika puzzle: Assessing the associated factors to microcephaly in a systematic review and meta-analysis.

Abstract: Background: Although it is known that Zika virus (ZIKV) infection during pregnancy may lead to microcephaly in the fetus, the prognostic factors associated with this tragic disorder remain unclear. We conducted a systematic review and meta-analysis to assess the prognostic factors associated with the incidence of microcephaly in congenital ZIKV infection. Methods: We conducted a comprehensive search in Ovid MEDLINE, Ovid MEDLINE (R) Epub ahead of print, Embase, Embase Classic, Web of Science, CINAHL, Cochrane … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…There are multiple reasons for the lack of laboratory-confirmation, which is a common feature of studies of CZS. 9,11,16 Firstly, a proportion of these children were born before ZIKV was first detected in Brazil (in October 2015). 1 Although there were reports of an unknown 'dengue-like' illness in North-Eastern Brazil in 2014 , phylogenetic and molecular clock analyses suggest that ZIKV was introduced into the Americas in the second half of 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple reasons for the lack of laboratory-confirmation, which is a common feature of studies of CZS. 9,11,16 Firstly, a proportion of these children were born before ZIKV was first detected in Brazil (in October 2015). 1 Although there were reports of an unknown 'dengue-like' illness in North-Eastern Brazil in 2014 , phylogenetic and molecular clock analyses suggest that ZIKV was introduced into the Americas in the second half of 2013.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of six studies found a relative risk of microcephaly of 0•68 (95% CI 0•60, 0•77) for asymptomatic versus symptomatic maternal ZIKV infection. 16…”
Section: Discussionmentioning
confidence: 99%
“…The teratogenicity and neuropathology associated with ZIKV might affect fetal growth across the placenta, selective to the central neural system [7]. Consequently, Gallo et al noticed that most severe brain anomalies, likely microcephaly, were linked with the rash during the first trimester of pregnancy [10]. França et al said the rash occurred earlier during pregnancy and the head size was smaller at birth [11].…”
Section: Zika's Virus Infection During Pregnancy and Its Impact On Ne...mentioning
confidence: 99%
“…Phylogenetic analyses have revealed two main ZIKV lineages, African and Asian, and the contemporary epidemics have been traced to the Asian lineage [2]. Currently, ZIKV has been causally linked to microcephaly during pregnancy and thus evolved into a new public health threat [3]. The genome of ZIKV is a positive-sense RNA that contains one open reading frame encoding a polyprotein, which can be cleaved into three structural proteins, including capsid (C), precursor membrane (PrM), and envelope (E), and seven nonstructural (NS) proteins [4,5].…”
Section: Introductionmentioning
confidence: 99%